EVALUATION OF THE PROTECTIVE EFFECT OF GALLIC ACID AGAINST ARSENIC-INDUCED GENOTOXICITY IN HEPG2 CELL LINE - JOSEPH, NIDHYA TERESA; MOKA, RAJASEKHAR (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Arsenic has cytotoxic as well as mutagenic effect in human health due to its indirect effect on oxidative stress on the cells. We aimed to find out the effect of gallic acid (GA), a well-known natural antioxidant in ameliorating in heavy metal toxicity. Methods: MTT assay was performed to determine the cytotoxicity of sodium arsenite (NaAsO2) on HepG2 cells with the cytoprotectant GA at varying concentrations for exposure durations of 6 h, 12 h, and 24 h. Similarly, the alkaline version of the comet assay was performed to investigate the genotoxicity and assessment of oxidative stress of the cells using flow cytometry. Results: Cells treated with NaAsO2 at various doses spanning a broad range of concentrations (5–500 μM) showed a dose- and time-dependent decrease in cellular viability as observed. However, the effect of the proposed protectant, GA showed an increase in cellular viability in a concentration-dependent manner. Conclusion: We assessed the cytotoxicity and genotoxicity induced by NaAsO2 to provide insight into the role of GA on arsenic-induced toxicity in liver cells and to shed light on its possible ameliorative effect at low concentrations in a time-dependent manner.